Fraction Four Operations

Easy

Medium

Difficult

Q1) \(\frac{3}{4}\) - \(\frac{2}{9}\) =
Q1) \(\frac{2}{3}\) \(\div\) \(\frac{1}{5}\) =
Q1) 1\(\frac{1}{4}\) + 1\(\frac{1}{3}\) =
Q2) \(\frac{3}{5}\) - \(\frac{4}{9}\) =
Q2) \(\frac{7}{8}\) x \(\frac{7}{8}\) =
Q2) 1\(\frac{3}{4}\) x 1\(\frac{1}{2}\) =
Q3) \(\frac{6}{7}\) - \(\frac{4}{5}\) =
Q3) \(\frac{3}{5}\) \(\div\) \(\frac{7}{9}\) =
Q3) 1\(\frac{1}{9}\) \(\div\) 1\(\frac{1}{4}\) =
Q4) \(\frac{2}{5}\) + \(\frac{3}{10}\) =
Q4) \(\frac{7}{10}\) \(\div\) \(\frac{9}{10}\) =
Q4) 1\(\frac{1}{5}\) x 1\(\frac{1}{2}\) =
Q5) \(\frac{4}{5}\) - \(\frac{1}{2}\) =
Q5) \(\frac{1}{5}\) \(\div\) \(\frac{3}{5}\) =
Q5) 2\(\frac{1}{4}\) - 1\(\frac{2}{11}\) =
Q6) \(\frac{1}{4}\) + \(\frac{1}{2}\) =
Q6) \(\frac{2}{3}\) x \(\frac{9}{10}\) =
Q6) 4\(\frac{1}{3}\) - 1\(\frac{4}{7}\) =
Q7) \(\frac{5}{6}\) - \(\frac{5}{7}\) =
Q7) \(\frac{7}{8}\) x \(\frac{8}{9}\) =
Q7) 2\(\frac{1}{2}\) \(\div\) 1\(\frac{1}{2}\) =
Q8) \(\frac{4}{5}\) - \(\frac{3}{4}\) =
Q8) \(\frac{7}{8}\) x \(\frac{4}{5}\) =
Q8) 2\(\frac{1}{2}\) + 1\(\frac{2}{3}\) =
Q9) \(\frac{5}{7}\) - \(\frac{2}{5}\) =
Q9) \(\frac{2}{3}\) \(\div\) \(\frac{3}{7}\) =
Q9) 2\(\frac{1}{4}\) x 3\(\frac{1}{3}\) =
Q10) \(\frac{1}{2}\) - \(\frac{3}{8}\) =
Q10) \(\frac{5}{8}\) \(\div\) \(\frac{8}{9}\) =
Q10) 1\(\frac{1}{5}\) x 1\(\frac{1}{3}\) =